Pressure-driven superconductivity in the transition-metal pentatelluride HfT e5 - Qi, Yanpeng; Shi, Wujun; Naumov, Pavel G.; Kumar, Nitesh; Schnelle, Walter; Barkalov, Oleg; Shekhar, Chandra; Borrmann, Horst; Felser, Claudia; Yan, Binghai; Medvedev, Sergey A. (Physical Review B, 2016)
The discovery of superconductivity in hafnium pentatelluride HfTe5 under high pressure is reported. Two structural phase transitions and metallization with superconductivity developing at around 5 GPa are observed. A maximal critical temperature of 4.8 K is attained at a pressure of 20 GPa, and superconductivity persists up to the maximum pressure of the study (42 GPa). The combination of electrical transport and crystal structure measurements as well as theoretical electronic structure calculations enables the construction of a phase diagram of HfTe5 under high pressure.
CRIS-Team Scopus Importer:2023-03-20